B. F. Skinner: Teórico da ciência e teórico da moral? - Zilio, Diego [UNESP]; Carrara, Kester [UNESP] (My University, 2009)
Would Skinner's moral theory be dependent on his scientific theory to the point of becoming meaningless without it? The mere suggestion of such hypothesis brings the problem of naturalistic fallacy, that is, the problem of deriving statements of ought kind from statements of is kind. This issue is used here as an indication that suggests how problematic sustaining a moral and a scientific theory in the same ambit can be. The aim of this article, in this context, is to analyze if that is the case of Radical Behaviorism. Inspired by the naturalistic fallacy dilemma, the first step is to expose the structural and functional differences between statements of ought kind and statements of is kind. To do so, the strategy is to present, under the scope of language philosophy, the differences between factual and valuative assertions. The next step consists in analyzing what the nature of relations between Skinner's scientific and moral theories is. That is, if there are necessary or contingencial relations. By doing so it is expected to be plausible the presentation of a possible answer to the central question of this article.
B. F. Skinner: Theorist of science and theorist of moral?
Keywords: Facts; Moral theory; Radical behaviorism; Scientific theory; Skinner; Values